2008
DOI: 10.2174/1874838400801010026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Analytical Methods for Detecting (1-3)-β-D-Glucan in Pure Fungal Cultures and in Home Dust Samples

Abstract: There are two methods available for the analysis of (1-3)--D-glucan: the Limulus Amebocyte Lysate assay (LAL) and the inhibition Enzyme Immunoassay (EIA). The aim of this study was to compare the accuracy and specificity of these two methods in detecting eight alpha and beta-glucan standards, and their sensitivity for the analysis of (1-3)--D-glucan content of common indoor fungal species and indoor dust samples. The results show that the LAL assay is more accurate, specific, and sensitive in measuring linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…The median concentration of b-glucan per g dust is higher and the loading (lg m -2 ) lower than what has been measured in Canadian homes (n = 28, EP and season nm) of asthmatic children (median = 190 lg g -1 dust and 160 lg m -2 floor) (Berghout et al 2005) as well as in floor dust from homes in the USA (geometric mean = 40 lg g -1 and 9 lg m -2 , EP: 60 min, season nm) (Iossifova et al 2008). Both the median concentration and loading is lower than found in carpeted (1,100 lg g -1 dust and 1,200 lg m -2 , n = 15, EP and season nm) and tiled floors (1,300 lg g -1 and 50 lg m -2 , n = 15, EP and season nm) in two schools in USA (Foarde and Berry 2004).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The median concentration of b-glucan per g dust is higher and the loading (lg m -2 ) lower than what has been measured in Canadian homes (n = 28, EP and season nm) of asthmatic children (median = 190 lg g -1 dust and 160 lg m -2 floor) (Berghout et al 2005) as well as in floor dust from homes in the USA (geometric mean = 40 lg g -1 and 9 lg m -2 , EP: 60 min, season nm) (Iossifova et al 2008). Both the median concentration and loading is lower than found in carpeted (1,100 lg g -1 dust and 1,200 lg m -2 , n = 15, EP and season nm) and tiled floors (1,300 lg g -1 and 50 lg m -2 , n = 15, EP and season nm) in two schools in USA (Foarde and Berry 2004).…”
Section: Discussionmentioning
confidence: 60%
“…Some methods are based on a b-glucan antigen-antibody reaction (Sander et al 2008) and another upon the bioactivity of b-glucan in the factor-G-mediated Limulus Amebocyte Lysate assay (LAL) (Foto et al 2004;Tamura et al 1994). Data obtained by one method using monoclonal antibodies and the LAL method are not directly comparable (Iossifova et al 2008) while another method also using monoclonal antibodies seems to give results comparable with results obtained by the LAL method on samples of airborne dust (Sander et al 2008). The LAL assay is commercially available but expensive and is widely used in Europe, Asia and USA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3)-glucan. These differences determine the AM arithmetic mean, SE standard error sensitivity of each method, which was described with details by Iossifova et al (2008). They indicated that the limit of detection (LOD) for LAL assay was 3.125 pg/ml, whereas for ELISA-250 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…3)-b-D-glucans. As indicated by Iossifova et al (2008), both methods are characterized by a completely different sensitivity level, which for the LAL method amounts to 3.125 pg/ml, whereas for the ELISA method-to 250 ng/ml. Heldal et al (2003) indicate that the comparison of the results from air samples obtained with the use of the above methods might lead to false conclusions.…”
Section: Discussionmentioning
confidence: 99%